Introducing Artificial Intelligence Utilization in Learning to High School Teachers - Djajasoepena, Rafie; Syamsuri, Ady; Nurfais, Ahmad; Bahagia, Katherine Luckman; Kusuma, Felicia; Dewa, Gilang Raka Rayuda; Purnomo, Ariana Tulus; Bhakti, Muhammad Agni Catur; Wandy, Wandy; Triawan, Farid; Githa, Arum; Lestari, Tika Endah; Setiawan, Iwan (Center for Research and Community Service of Sampoerna University, 2025)
The development of artificial intelligence (AI) has significantly impacted various sectors, including education. However, based on observation, no AI tool-integrated course has been utilized by teachers at SMA 6 Cirebon. Moreover, based on the pretest assignment, the average understanding of teachers in SMAN 6 Cirebon regarding AI technology was only 55.48%, indicating challenges in implementing AI tools due to a lack of knowledge and practical guidance. To address this issue, a community service activity was held to empower teachers with applicable AI knowledge and skills through a seminar titled